2011
DOI: 10.1590/s1020-49892011000400005
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of rubella after mass vaccination of children and adult women: challenges for rubella elimination strategies

Abstract: Routine vaccination strategies and mass vaccination of adolescents and adults for accelerated rubella control and elimination should target men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…7 During the last few years, many countries have reported outbreaks of rubella infection. 11,12 However, to our knowledge, available data in the literature dealing with rubella encephalitis are scarce and are limited to several case reports. 9,13 Tunisian public health care authorities reported in 2011 an important increase of patients admitted to hospitals because of eruptive fever.…”
Section: Discussionmentioning
confidence: 99%
“…7 During the last few years, many countries have reported outbreaks of rubella infection. 11,12 However, to our knowledge, available data in the literature dealing with rubella encephalitis are scarce and are limited to several case reports. 9,13 Tunisian public health care authorities reported in 2011 an important increase of patients admitted to hospitals because of eruptive fever.…”
Section: Discussionmentioning
confidence: 99%
“…24 Combined vaccination strategy with a risk population approach for adults (WCBA, college students, health care workers, teachers, military personnel, government employees, and industry employees) and universal vaccination for boys and girls could be more efficient in reducing the incidence of acquired rubella and CRS as observed in Brazil, the US, and Cuba. [26][27][28][29] The review concluded that a combined vaccination strategy with routine vaccination for boys and girls and universal vaccination for adolescents and adults (both men and women), aged 15-39 years, through "speed-up" campaigns, was the most effective strategy. 22 This strategy reduced rubella incidence by more than 98%, and no CRS was reported since 2008 in Mexico and Costa Rica.…”
mentioning
confidence: 99%